2020
DOI: 10.29173/cjs29434
|View full text |Cite
|
Sign up to set email alerts
|

Conjugal Love from a Sociological Perspective: Theorizing from Observed Practices.

Abstract: This paper presents a sociological reflection on contemporary conjugal love, both from an empirical and a theoretical point of view. Drawing on analyses of data regarding financial arrangements between partners forming a couple, as well as on the sociological literature concerning love relationships, we present a theorization of contemporary conjugal semantics. We define these semantics as consisting of eight “meaning rules” through which social actors respond to the challenges of intimate relationships. Our a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Through this cultural integration, the immigrant hopes to achieve or enable his descendants to achieve structural integration, which is participation in collective life and above all the invention of rules in the community that adopted him Schnapper [16]. However, even if for the spouses interviewed, their union is the pure and simple result of their love, it should however be noted that for the social actors, it is an investment from which each expects to derive a profit, either material [17] or symbolic [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through this cultural integration, the immigrant hopes to achieve or enable his descendants to achieve structural integration, which is participation in collective life and above all the invention of rules in the community that adopted him Schnapper [16]. However, even if for the spouses interviewed, their union is the pure and simple result of their love, it should however be noted that for the social actors, it is an investment from which each expects to derive a profit, either material [17] or symbolic [18].…”
Section: Discussionmentioning
confidence: 99%
“…To this end, Dozon [17], in a socio-economic analysis in Côte d'Ivoire, affirms that the natives, to differentiate themselves from other ethnic groups, rely on the identity differentiation between them and non-natives. For him, economic reasons are the basis of this distinction.…”
Section: Discussionmentioning
confidence: 99%
“…As recent studies have shown, individuals' sexual identity is not fixed, and may not always align with one's partnership status or their sexual behavior (Hu & Denier, 2023;Mittleman, 2023;Silva, 2019;Silva & Fetner, 2022). While it is suboptimal that the LAD does not offer a direct measure of sexual identity, it allows us to consider individuals' partnership practices, assuming co-residential partnership indicates, on balance, a certain degree of financial, social and emotional interdependence in a joint household (Belleau et al, 2020). 8…”
Section: Opportunities For Research On Sexual Minorities With the Ladmentioning
confidence: 99%
“…In contrast to transaction cost theories, institutional approaches to conjugal economies posit that not just practical concerns and relationship trust, but also norms of conjugal behavior guide couples in their resource organization (Belleau et al., 2020; Stocks et al., 2007; Yodanis & Lauer, 2007). Although those norms were once relatively homogenous under the male breadwinner model, inviting men to financially provide for their caretaking wives, multiple ideals have come to coexist (Belleau et al., 2020; Cherlin, 2004; Evertsson & Nyman, 2014). One of them calls for independence in romantic relationships (Beck & Beck‐Gernsheim, 1995; Giddens, 1992).…”
Section: Institutional Approaches and Conjugal Solidarity Normsmentioning
confidence: 99%